Strengthening the Health System to Address the COVID-19 Surge: An Empirical Study in South Kalimantan Province, Indonesia - Putro, Gurendro; Ristrini, Ristrini; Pane, Masdalina; Widya Sukoco, Noor Edi; Rahayu, Nita; Rustika, Rustika; Nirwan, Muhammad; Ariani Kurniasih, Dea Anita; Noviani, Lusy; Balumbi, Musthamin (International Journal of Statistics in Medical Research, 2025)
The COVID-19 case entered South Kalimantan Province on May 12, 2020, and spread throughout all districts/cities. This research aims to examine the ability of the South Kalimantan Provincial Health System to address the COVID-19 pandemic. This study analyses secondary data from the South Kalimantan Provincial Health Office and in-depth interviews with policymakers. This study assesses the capacity of the South Kalimantan health system in managing the COVID-19 pandemic. Findings reveal significant challenges, including hospital bed shortages, high infection rates among health workers (10.02%), and limited ventilator availability. Despite allocating 23.27% of the health budget to the pandemic response, key subsystems such as human resources, drug supply, and coordination mechanisms remained under strain. Strengthening these subsystems is essential for better preparedness in future health emergencies. In conclusion, strengthening the health system is very important in overcoming the COVID-19 pandemic, and it is hoped that the lessons of the COVID-19 pandemic will make the health system more prepared to address the disease pandemic.